2017
DOI: 10.1111/liv.13396
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family history of metabolic traits on severity of non‐alcoholic steatohepatitis related cirrhosis: A cross‐sectional study

Abstract: Family and personal history of metabolic traits are associated with early age at diagnosis of cirrhosis with more severity and decompensation and so, has a prognostic importance in NASH-related cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In a seminal study, Loomba et al had shown the importance of family and personal history of diabetes on natural history of NAFLD with a higher proportion of these patients having NASH with advanced fibrosis. Recently, we demonstrated that the presence of a positive family history (among first degree relatives) of metabolic traits has a significant impact on the younger age at diagnosis and more severity of NASH‐related cirrhosis . In this novel study, for the first time, it has been demonstrated that the presence of family and personal history of metabolic traits led to alcoholic cirrhosis at a younger age with increased incidence of decompensation despite lesser amount and duration of alcohol consumption compared to those cirrhotics without positive family or personal history of metabolic traits.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a seminal study, Loomba et al had shown the importance of family and personal history of diabetes on natural history of NAFLD with a higher proportion of these patients having NASH with advanced fibrosis. Recently, we demonstrated that the presence of a positive family history (among first degree relatives) of metabolic traits has a significant impact on the younger age at diagnosis and more severity of NASH‐related cirrhosis . In this novel study, for the first time, it has been demonstrated that the presence of family and personal history of metabolic traits led to alcoholic cirrhosis at a younger age with increased incidence of decompensation despite lesser amount and duration of alcohol consumption compared to those cirrhotics without positive family or personal history of metabolic traits.…”
Section: Discussionmentioning
confidence: 72%
“…Loomba et al showed that personal history and family history of diabetes were independently associated with increased risk of progression to non‐alcoholic steatohepatitis (NASH) and advanced fibrosis. We recently reported that the presence of family and personal history of metabolic traits such as diabetes, hypertension, dyslipidaemia, coronary artery disease and obesity is associated with early age at diagnosis of NASH‐related cirrhosis with more severity and decompensation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported high odds of cirrhosis with familial and personal history of MTs in the presence of certain identified poor hepatic-related prognostic factors compared with those who had negative familial and personal history. [8] The identified poor hepatic-related prognostic factors were high severity scores such as Child–Turcotte–Pugh score and model for end-stage liver disease score, with ≥1 features of decompensation such as ascites, jaundice, hepatic encephalopathy, and variceal bleeding. [8] Another recent study has documented presence of ≥1 components of metabolic syndrome among patients with NAFLD with significant steatosis and fibrosis as identified by transient elastography.…”
mentioning
confidence: 99%
“…[8] The identified poor hepatic-related prognostic factors were high severity scores such as Child–Turcotte–Pugh score and model for end-stage liver disease score, with ≥1 features of decompensation such as ascites, jaundice, hepatic encephalopathy, and variceal bleeding. [8] Another recent study has documented presence of ≥1 components of metabolic syndrome among patients with NAFLD with significant steatosis and fibrosis as identified by transient elastography. [9]…”
mentioning
confidence: 99%